Development of Transdisciplinary and Complex Learning in Inclusive Educational Practices - Nerea Hernaiz-Agreda; María Dolores Soto-González; Ramona Rodríguez-López (MDPI AG, 2024)
This study examines the process of creating digital resources to meet the specific educational needs of primary education students at a school in the province of Valencia (Spain). The resources were developed by students of the Teaching program at the University of Valencia as part of the special educational needs subject. The research focuses on transdisciplinarity and the use of new technologies and sustainable development objectives to enrich the educational experience at the school as well as to study this approach with students pursuing a bachelor's degree in Primary Education. To analyze students' perceptions of this practice and compare their reflective and transdisciplinary thinking, a validated questionnaire was administered to a sample of 39 participants. In addition, seven focus groups were organized. The results demonstrate that via transdisciplinarity and the use of technological resources, students enhance their abilities to address complex situations, fostering creativity and innovation by relating different areas of knowledge in real and contextualized settings. Furthermore, an increase in reflective capacity and research skills is highlighted, contributing to better understanding and learning based on digital technologies.